2017
DOI: 10.3389/fpsyt.2017.00035
|View full text |Cite
|
Sign up to set email alerts
|

The Reciprocal Relationship between Suicidality and Stigma

Abstract: IntroductionAlthough suicidality is frequently the cause of stigma, it is conversely true that stigma may be the cause of suicidality. The present paper focuses on the complex relationships that exist between suicidal behavior and stigmatizing attitudes.MethodsA narrative review of the topic will be presented on the basis of the relevant literature collected from an electronic search of PubMed, ISI Web of Knowledge, and Scopus databases, using stigma, public stigma, structural stigma, perceived stigma, self-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
123
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 106 publications
2
123
0
8
Order By: Relevance
“…Suicide stigma, defined as negative attitudes toward suicidal individuals, may similarly lead to a range of negative outcomes, therefore representing an important intervention target for suicide prevention. Stigma has been shown to increase suicide risk (Carpiniello & Pinna, ; Sharaf, Ossman, & Lachine, ), while personal stigma toward suicidal people may reduce engagement with professional services (Han, Batterham, Calear, & Randall, ; Hom, Stanley, & Joiner, ) and lead to more negative attitudes regarding professional service use (Calear, Batterham, & Christensen, ). Other attitudes about suicide, such as glorification of suicide, or attribution of suicide to isolation, may also impact upon outcomes for individuals experiencing suicidal thoughts (Calear et al., ; Chan, Batterham, Christensen, & Galletly, ).…”
mentioning
confidence: 99%
“…Suicide stigma, defined as negative attitudes toward suicidal individuals, may similarly lead to a range of negative outcomes, therefore representing an important intervention target for suicide prevention. Stigma has been shown to increase suicide risk (Carpiniello & Pinna, ; Sharaf, Ossman, & Lachine, ), while personal stigma toward suicidal people may reduce engagement with professional services (Han, Batterham, Calear, & Randall, ; Hom, Stanley, & Joiner, ) and lead to more negative attitudes regarding professional service use (Calear, Batterham, & Christensen, ). Other attitudes about suicide, such as glorification of suicide, or attribution of suicide to isolation, may also impact upon outcomes for individuals experiencing suicidal thoughts (Calear et al., ; Chan, Batterham, Christensen, & Galletly, ).…”
mentioning
confidence: 99%
“…They are attributed to a number of factors, some of which inform societal impressions of the person who are suicidal. These impressions are that the person is weak, selfish, attention seeking, a failure, or unworthy (Carpiniello & Pinna ; Vatne & Nåden ). The results of our study indicate that nurses’ beliefs in religion and subsequently people's observance of religion or religious beliefs are representative of individual coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study indicate that nurses’ beliefs in religion and subsequently people's observance of religion or religious beliefs are representative of individual coping strategies. Another study demonstrated that prejudicial attitudes towards people who attempt suicide exist, with participants indicating that these actions are ‘punitive, selfish, offensive, or reckless’ (Carpiniello & Pinna ). Shame and blame lead to stigma, which by its nature is discriminatory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…nível dos cuidados de saúde primários; melhoria da informação e educação em saúde mental; sensibilização dos meios de comunicação para a necessidade de aplicação dos princípios definidos para a informação/descrição de comportamentos autolesivos e atos suicidas; diminuição do estigma em torno da depressão, ideação suicida, comportamentos autolesivos e atos suicidas. [11][12][13] Com este trabalho pretende-se estudar a realidade da consulta da Unidade de Comportamentos Suicidários (UCS) do Hospital de Braga, através de uma análise estatística de caráter descritivo e analítico.…”
Section: Introductionunclassified